PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN CANVA PADA MATA PELAJARAN DASAR-DASAR PROGRAM KEAHLIAN TEKNIK JARINGAN KOMPUTER DAN TELEKOMUNIKASI KELAS X TKJ 2 DI SMK SORE TULUNGAGUNG - Ahmat Rifaul, Febri; Haris Indrakusuma, Abdul; Panggayuh, Vertika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the learning process in the Basic Subjects of Computer and Telecommunications Network Engineering for Class X TKJ 2 at SMK Sore Tulungagung, where the learning media still relied on Microsoft PowerPoint with a simple and less interactive design. The presentation of the material was dominated by text with limited use of images, animations, and other visual elements, resulting in low student interest and engagement during the learning process. This study aimed to develop interactive learning media using Canva and determine the feasibility of the developed media. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research data were collected through observation, interviews, and questionnaires. The research subjects consisted of one media expert, one subject matter expert, nine students in the small-group trial, and thirty students in the large-group trial. The data were analyzed using descriptive quantitative techniques through feasibility percentage calculations. The results showed that the interactive learning media developed using Canva obtained a feasibility score of 97.9% from the media expert validation and 97.3% from the subject matter expert validation. The small-group trial produced a feasibility score of 97.6%, while the large-group trial obtained 98.7%. All assessment results were categorized as "Highly Feasible." Therefore, it can be concluded that the interactive learning media developed using Canva is highly feasible to be used as a learning medium for the Basic Subjects of Computer and Telecommunications Network Engineering in Class X TKJ 2 at SMK Sore Tulungagung.